Is Nonoperative Treatment Appropriate for All Patients With Type 1 Tibial Spine Fractures? A Multicenter Study of the Tibial Spine Research Interest Group. Issue 6 (3rd June 2022) - Shimberg, Jilan L.; Leska, Tomasina M.; Cruz, Aristides I.; Ellis, Henry B.; Patel, Neeraj M.; Yen, Yi-Meng; ,; Schmale, Gregory A.; Mistovich, R. Justin; Fabricant, Peter D.; Ganley, Theodore J.; Green, Daniel W.; et al.
Background: Type 1 tibial spine fractures are nondisplaced or ≤2 mm–displaced fractures of the tibial eminence and anterior cruciate ligament (ACL) insertion that are traditionally managed nonoperatively with immobilization. Hypothesis: Type 1 fractures do not carry a significant risk of associated injuries and therefore do not require advanced imaging or additional interventions aside from immobilization. Study Design: Case series; Level of evidence, 4. Methods: We reviewed 52 patients who were classified by their treating institution with type 1 tibial spine fractures. Patients aged ≤18 years with pretreatment plain radiographs and ≤ 1 year of follow-up were included. Pretreatment imaging was reviewed by 4 authors to assess classification agreement among the treating institutions. Patients were categorized into 2 groups to ensure that outcomes represented classic type 1 fracture patterns. Any patient with universal agreement among the 4 authors that the fracture did not appear consistent with a type 1 classification were assigned to the type 1+ (T1+) group; all other patients were assigned to the true type 1 (TT1) group. We evaluated the rates of pretreatment imaging, concomitant injuries, and need for operative interventions as well as treatment outcomes overall and for each group independently. Results: A total of 48 patients met inclusion criteria; 40 were in the TT1 group, while 8 were in the T1+ group, indicating less than universal agreement in the classification of these fractures. Overall, 12 (25%) underwent surgical treatment, and 12 (25%) had concomitant injuries. Also, 8 patients required additional surgical management including ACL reconstruction (n = 4), lateral meniscal repair (n = 2), lateral meniscectomy (n = 1), freeing an incarcerated medial meniscus (n = 1), and medial meniscectomy (n = 1). Conclusion: The classification of type 1 fractures can be challenging. Contrary to prior thought, a substantial number of patients with these fractures (>20%) were found to have concomitant injuries. Overall, surgical management was performed in 25% of patients in our cohort.